Geothermal Pipeline - Geo-Heat Center (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 2000)
Senate Republicans unveiled an energy policy bill that aims to offset foreign oil imports by as much as 50% by maximizing electricity production from alternative energy sources and boosting domestic oil production. The legislative proposal also contains tax incentives for electricity produced from renewable energy sources, such as wind, solar and “biomass.” It also promotes power produced by hydro-electric, nuclear and coal-fired plants. Senate Majority Leader Trent Lott (R., Miss.) and Senate Energy Committee Chairman Frank Murkowski (R., Alaska) support the bill, which Lott said, “isn’t just about increasing oil production, but about boosting energy production from coal, solar, wind and other sources